2019
DOI: 10.1002/smll.201804533
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 and Co Nanoparticle‐Decorated Carbon Polyhedra as Efficient Sulfur Host for High‐Performance Lithium–Sulfur Batteries

Abstract: Metal organic frameworks (MOFs)‐derived porous carbon is proposed as a promising candidate to develop novel, tailorable structures as polysulfides immobilizers for lithium–sulfur batteries because of their high‐efficiency electron conductive networks, open ion channels, and abundant central ions that can store a large amount of sulfur and trap the easily soluble polysulfides. However, most central ions in MOFs‐derived carbon framework are encapsulated in the carbon matrix so that their exposures as active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…[16,17] For example, transition-metal oxides (TMOs) with abundant of active adsorption sites, which can chemically adsorb LiPSs and retain their capability, are regarded as effective sulfur hosts. [18][19][20][21][22][23] In addition, more and more TMOs have been certified to be beneficial to the conversion kinetics of intermediate LiPSs due to their catalytic effects. [6,[24][25][26] As typical TMOs, with the advantages of environmental friendliness and low cost, zinc oxide based nanomaterials have attracted lots of attention in the field of Li−S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] For example, transition-metal oxides (TMOs) with abundant of active adsorption sites, which can chemically adsorb LiPSs and retain their capability, are regarded as effective sulfur hosts. [18][19][20][21][22][23] In addition, more and more TMOs have been certified to be beneficial to the conversion kinetics of intermediate LiPSs due to their catalytic effects. [6,[24][25][26] As typical TMOs, with the advantages of environmental friendliness and low cost, zinc oxide based nanomaterials have attracted lots of attention in the field of Li−S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is rarely reported in the previous studies toward using TiO 2 -based materials as the sulfur hosts. [22,28,52,62] Based on the above discussion, a dual chemical mediation mechanism for LiPSs, namely, strong surface polarpolar interaction coupled with thiosulfate/polythionate conversion, is demonstrated by the proposed TiC@C-TiO 2 composite in this study. The regulation mechanism of LiPSs is displayed in Figure 5d.…”
Section: Adsorption and Chemical Interactionmentioning
confidence: 67%
“…Nevertheless, the polar LiPSs still tend to move out of the cathode due to their weak interfacial interaction with nonpolar carbonaceous materials. [20] To this end, polar materials, such as heteratom-doped carbon, [21] transitional metal oxides, [22] metal sulfides, [23] metal nitrides, [24] metal carbides, [25] and metal borides [26] with a strong chemical affinity toward LiPSs, have been developed to effectively mitigate the notorious shuttle effect of LiPSs and achieve long-term cycling stability.…”
Section: The Performance Of Lithium-sulfur (Li-s) Batteries Is Greatlmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, since Co-NDs@G is developed through the calcination of ZIF-67@GO (N, Cocontaining precursor), it is difficult to directly distinguish the effects of Co and N on the battery performances. However, it was reported that Co nano-dots [44] and N-doped graphene [45] both can have positive effects on lithium-sulfur batteries. Moreover, our DFT calculations also showed that metal Co, Co-N-C, and Ndoped graphene sites exhibits high binding energy towards polysulfide species.…”
Section: Resultsmentioning
confidence: 99%